A Novel Echocardiographic Index (Modified-Left-Atrium-to-Aorta Ratio) for Quantifying Left Atrial Size and Differentiating Stages in Dogs with Myxomatous Mitral Valve Disease - Minsuk Kim; Minwoong Seo; Chul Park (Animals, 2025)
Myxomatous mitral valve disease (MMVD) is the most common heart disease in small-breed dogs, and accurate assessment of the left atrial (LA) size is essential for diagnosis and management. The traditional echocardiographic method, LA-to-Aorta (LA/Ao) ratio, is widely used, but evaluates LA size in only one view. This study introduces a novel index—the modified-LA/Ao (M-LA/Ao) ratio—which combines two echocardiographic views to better reflect the true LA size. This study retrospectively analyzed thoracic radiographs and echocardiograms from 136 dogs, including healthy controls and dogs with MMVD classified into stages B1, B2, and C according to ACVIM guidelines. The ability of the M-LA/Ao ratio is compared to conventional indices using correlation analysis and receiver operating characteristic (ROC) curves. The M-LA/Ao ratio showed a strong correlation with existing indices and slightly improved discrimination between ACVIM stages B1 and B2, although performance between stages B2 and C was similar to the LA/Ao ratio. Intra- and interobserver variability were also acceptable. Our findings suggest that the M-LA/Ao ratio may provide a practical and sensitive method to evaluate LA enlargement in early-stage MMVD, helping clinicians detect subtle cardiac remodeling before progression to advanced disease.